Nivel de satisfacción de las gestantes atendidas en el Consultorio de atención prenatal del Hospital Amazónico – Yarinacocha. Julio–Setiembre 2013 - Saldaña Shupingahua, Baleny (2014)
The present study titled satisfaction of pregnant women at the office of the Amazon Prenatal Care Hospital - Yarinacocha July - September 2013; aimed to Determine the level of satisfaction of pregnant women at the antenatal clinic. Quantitative, descriptive, prospective, cross-sectional study. This was a survey instrument consisted of 10 questions with closed answers With a minimum score 10 points and the maximum 50 points was classified into Low, medium and high. The sample consisted of 200 pregnant women who met The inclusion criteria, being the art of non-probability convenience sampling. The findings, reported that 100% reported that he received good treatment, 85% reported that gave him confidence, 100% of pregnant women report that The staff that you explained about the test that was going to make 100% rate Understandable as the language used by the professional, 99% reported that They explained about evolution, pregnancy care and follow at home; on the Duration of the query 65% of pregnant women report that was adequate, 75% Relates to wait long to be served and 60% indicate that they are comfortable With the service. In conclusion, the hypothesis is not accepted because there is a higher level of Satisfaction (91%) of the pregnant women at the antenatal clinic.